A review of stalk-eyed fruit flies (Diptera: Tephritidae: Trypetinae) - Chen, Xiaolin; Zhang, Yanzhou; Li, Jie; Zhu, Chaodong (Zootaxa, 2010)
Species of stalk-eyed fruit flies of the genera Pelmatops Enderlein and Pseudopelmatops Shiraki are reviewed and discussed; a key to the two genera and eight species is given. Pelmatops tangliangi Chen sp.nov., Pseudopelmatops indiaensis Chen sp.nov. and Pseudopelmatops yunnanensis Chen sp.nov. from the Oriental Region are described and illustrated.